Phenotypic Profile of Mycobacterium tuberculosis-Specific CD4 T-Cell Responses in People With Advanced Human Immunodeficiency Virus Who Develop Tuberculosis-Associated Immune Reconstitution Inflammatory Syndrome. (17th October 2022) - Moseki, Raymond M; Barber, Daniel L; Du Bruyn, Elsa; Shey, Muki; Van der Plas, Helen; Wilkinson, Robert J; Meintjes, Graeme; Riou, Catherine
Abstract: Background: Tuberculosis-associated immune reconstitution inflammatory syndrome (TB-IRIS) is a frequent complication of cotreatment for TB and human immunodeficiency virus (HIV)-1. We characterized Mycobacterium tuberculosis (Mtb)-specific CD4 T-cell phenotype and transcription factor profile associated with the development of TB-IRIS. Methods: We examined the role of CD4 T-cell transcription factors in a murine model of mycobacterial IRIS. In humans, we used a longitudinal study design to compare the magnitude of antiretroviral therapy, activation, transcription factor profile, and cytotoxic potential of Mtb-specific CD4 T cells between TB-IRIS ( n = 25) and appropriate non-IRIS control patients ( n = 18) using flow cytometry. Results: In the murine model, CD4 T-cell expression of Eomesodermin (Eomes), but not Tbet, was associated with experimentally induced IRIS. In patients, TB-IRIS onset was associated with the expansion of Mtb-specific IFNγ + CD4 T cells ( P = .039). Patients with TB-IRIS had higher HLA-DR expression ( P = .016), but no differences in the expression of T-bet or Eomes were observed. At TB-IRIS onset, Eomes + Tbet + Mtb-specific IFNγ + CD4 + T cells showed higher expression of granzyme B in patients with TB-IRIS ( P = .026). Conclusions: Although the murine model of Mycobacterium avium complex-IRIS suggests that Eomes + CD4 T cells underly IRIS, TB-IRIS was not associated with Eomes expression in patients. Mycobacterium tuberculosis -specific IFNγ + CD4 T-cell responses in TB-IRIS patients are differentiated, highly activated, and potentially cytotoxic.